Odpowiedzi

Najlepsza Odpowiedź!
2009-11-28T20:25:42+01:00
(1/2 + 2/5 *1/2)+9/10-5/6=
= (1/2+1/5)+27/30-25/30=
= 5/10+4/10+2/30=
9/10+2/30=
27/30+2/30=
29/30

chyba tyle ;-)
2 5 2
2009-11-28T20:28:42+01:00
(1/2 + 2/5 *1/2)+9/10-5/6=(½+⅖*½)+0,9-⅚=(½+⅕)+0,9-⅚=0,7+0,9-⅚=1,6-⅚=8/5-5/6=48/30-25/30=23/30
2 5 2
2009-11-28T20:29:09+01:00
(1/2 + 2/5 * 1/2 ) + 9/10 - 5/6 = (1/2 + 1/5) + 9/10 - 5/6 = (5/10 + 2/10) + 27/30 - 25/30 = 7/10 + 2/30 = 21/30 + 2/30 = 23/30

Ale mogłam się pomylić!! Starałam się żeby było dobrze ;-)
1 5 1